1975
DOI: 10.1088/0022-3727/8/13/008
|View full text |Cite
|
Sign up to set email alerts
|

The topography of laser-irradiated germanium

Abstract: Considerable interest centres around the use of germanium as a reflector material in high-power carbon-dioxide lasers. An important problem is the damage caused to the mirror surface as the result of the dynamic development of imperfections. This damage may be caused by an interference process which has been described previously. A characteristic of the damage which occurs is the melting of the germanium followed by resolidification. The authors describe a certain type of melting pattern which depends upon den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The new feature of the proposed model is the inclusion of thermally induced plastic effects. It was shown that the increased size of the affected area due to heating under the laser irradiation conditions used, may not be interpreted via other conventional physical mechanisms, such as melting 51,52 or ablation 26 , which do not sufficiently quantify the measured dimensions of the resulting spot size. Although the proposed scenarios may adequately describe, at least qualitatively, the underlying physical processes, the assumption that the related phenomena are confined in a region inside the laser beam spot area underestimates the contribution of the thermal stress deformation.…”
Section: Resultsmentioning
confidence: 99%
“…The new feature of the proposed model is the inclusion of thermally induced plastic effects. It was shown that the increased size of the affected area due to heating under the laser irradiation conditions used, may not be interpreted via other conventional physical mechanisms, such as melting 51,52 or ablation 26 , which do not sufficiently quantify the measured dimensions of the resulting spot size. Although the proposed scenarios may adequately describe, at least qualitatively, the underlying physical processes, the assumption that the related phenomena are confined in a region inside the laser beam spot area underestimates the contribution of the thermal stress deformation.…”
Section: Resultsmentioning
confidence: 99%
“…T m is the to solid is 6%. 21,28 The solid curve in Fig. 5(b) shows the simulated spectrum calculated using the phonon confinement model after accounting for stress originating from the interface energy, solidification expansion, and differential thermal expansion.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…레이저 조사가 종료 되어 용융된 게르마늄이 고체로 재응고될 때, 용융 연 못의 대류와 점성에 의해Fig. 7과같이 원뿔 모양의 hillock이 형성된다[14] . 그러므로 표면 변화가 나타난 곳까지 레이저 조사에 의해 용융온도 이상으로 온도 같이 측정치가 계산치보다 5.9 % 정도 크게 측정되었 으며, 조건 B로 실험한Fig.…”
unclassified